THE INFLUENCE OF SOCIAL MEDIA, BRANDING STRATEGY, AND E-SERVICE QUALITY MEDIA ON PURCHASE DECISIONS THROUGH DIGITAL LITERACY OF PANDESARI MSME PRODUCTS - Yusuf Purwanto; Agung Winarno; Wening Patmi Rahayu (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2024)
Consumer purchasing decisions are critical for businesses, necessitating the implementation of effective strategies to attract attention and secure buyers for their products. Factors influencing these decisions include social media, branding strategies, and the quality of e-services, all of which must be optimally managed to achieve the best results. In this study, a quantitative research method was employed. Data analysis was conducted using Partial Least Square (PLS), a variance-based approach to Structural Equation Modeling (SEM). The bootstrapping analysis of all variables revealed P-values below 0.005, indicating that all hypotheses were accepted. Consequently, the analysis demonstrates that social media, branding strategy, and e-service quality significantly impact purchase decisions through digital literacy.